Digital collaboration in Higher Education: Vulnerabilities and Challenges in E-Learning During Covid-19 pandemic - Andra Diaconescu (Communications of International Proceedings, 2020)
Digital industry influences the educational environment and encourages students to get actively involved, take part but also collaborate in this major change to overcome internal and external vulnerabilities in the learning process. Academia researchers are analyzing the vulnerabilities of this new digital revolution and trying to secure the online environment in higher education. Over the years, as innovations and investments in the digital space have grown considerably, so have opportunities for universities by allowing students to learn in their rhythm. This research seeks a detailed analysis of the most important tools that support digital collaboration among students given the current situation of online education in the COVID's context-19 pandemic. The tools that support digital collaboration among students facilitate communication in the current situation, increasing the opportunities for academia to interact with as many users as possible. Educators, students and administrators of online educational platforms need a sustainable basis for adopting a change in education. For educators, the availability of a real-time understanding is needed to increase student performance. For students, receiving information about their performance relative to their peers or their progress relative to their personal goals can be motivating and encouraging.
Keywords: Digital Collaboration; Challenges; Online; Higher Education; COVID-19